2002
DOI: 10.2337/diabetes.51.2.392
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Insulin-Like Growth Factor-2 Production Is Impaired in the GK Rat Model of Type 2 Diabetes

Abstract: At late fetal age (21.5 days postcoitum [dpc]), GK rats present a severely reduced ␤-cell mass compared with Wistar rats. This anomaly largely antedates the onset of hyperglycemia in GK rats. Thus, the ␤-cell mass deficit could represent the primary defect leading to type 2 diabetes in the adult. The aim of this work was to investigate, in GK fetuses at the end of fetal age (21.5 dpc), whether impaired availability of growth factors such as insulin, growth hormone, and IGFs and their IGF binding proteins (IGFB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 37 publications
5
28
0
Order By: Relevance
“…Our present findings are consistent with the maintenance of IGF2 responsiveness in GK beta cells and their cell precursors in pancreatic rudiments. Moreover, these data are in agreement with previous results demonstrating that IGF1 and IGF2 stimulated beta cell replication in fetal GK isolated islets [5]. Some factors such as hepatocyte growth factor and glucagon-like peptide 1 are known to influence the differentiation of progenitors into endocrine cells [13].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our present findings are consistent with the maintenance of IGF2 responsiveness in GK beta cells and their cell precursors in pancreatic rudiments. Moreover, these data are in agreement with previous results demonstrating that IGF1 and IGF2 stimulated beta cell replication in fetal GK isolated islets [5]. Some factors such as hepatocyte growth factor and glucagon-like peptide 1 are known to influence the differentiation of progenitors into endocrine cells [13].…”
Section: Discussionsupporting
confidence: 92%
“…We have previously shown that hepatic and pancreatic Igf2 mRNA were reduced at the end of fetal GK life [5].…”
mentioning
confidence: 92%
“…1 and Table 1). These data confirm and extend our earlier reports of decreased transcript levels of Pdx1, Neurog3 (also known as Ngn3) and Igf2 [16,18] and reduction in pancreatic IGF2 and IGF1R protein levels [16] in E18.5 GK stock fetuses.…”
Section: Resultssupporting
confidence: 81%
“…Defective signalling through the IGF2/IGF1-R pathway may represents the primary instrumental anomaly since IGF2 and IGF1-R protein expressions are already decreased within the GK/Par pancreatic rudiment at E13, at a time when beta-cell mass (first wave of beta cell expansion) is in fact normal (Miralles & Portha, 2001). Low levels of pancreatic IGF2, associated with beta-cell mass deficiency, are maintained thereafter within the fetal pancreas (Serradas et al, 2002). Crossbreeding protocols between non-diabetic W and diabetic GK rats showed that in late gestation (E18), pancreatic IGF2 protein expression was as low in GKmother/GKfather and Wmother/GKfather crosses than in GKmother/GK father crosses (Serradas et al, 2002).…”
Section: Molecular Mechanisms Mediating the Perinatal Beta-cell Adaptmentioning
confidence: 99%